PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN TOTAL ASSET TURN OVER (TATO) TERHADAP RETURN ON EQUITY (ROE) PADA PT ACE HARDWARE INDONESIA TBK PERIODE 2014-2023 - Cindy Aprilyani; Muhamad Nurhamdi (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Return On Equity at PT Ace Hardware Indonesia Tbk for the period 2014-2023. This type of research is descriptive quantitative with the analysis method used is descriptive statistics, classical assumption test, hypothesis test (t test and F test) with a significance level of 0.05 (5%) and the data source used is secondary data. The results of this study indicate that the Current ratio partially does not have a partial effect on Return On Equity, this is evidenced by the t test that the t-count value is 1.398 <ttable value of 2.44691 and has a significance number of 0.212 <0.05. The results of this study indicate that Debt to Equity Ratio partially does not affect Return On Equity, this is evidenced by the t test that the t count value is 0.984 <t table value of 2.44691 and has a significance figure of 0.363> 0.05. The results of this study indicate that Total Asset Turnover partially affects Return On Equity, this is evidenced by the t test that the t count value is 7.340> t table value of 2.44691 and has a significance figure of 0.000 <0.05. Simultaneous testing shows that Current Ratio, Debt To Equity Ratio, and Total Asset Turnover have a significant effect on Return On Equity, this is evidenced by the F test that the F count value is 29.139> F table value of 4.76 with a significance level of 0.001 <0.05